Analysis of Social Interaction of Grade IV Elementary School Students During the Covid-19 Pandemic - Afriani, Mayang; Ramadan, Zaka Hadikusuma (International Journal of Elementary Education, 2021)
The impact of Covid-19 by limiting social interaction is also experienced by students. But social interaction is needed for a child to be able to build character and social skills in interacting with other people. This study was conducted to answer the research question, namely how social interaction during the COVID-19 period, grade IV elementary school in Pekanbaru. Based on this, the purpose of this research is to examine the pattern of social interaction during the COVID-19 period, grade IV elementary school in Pekanbaru. The research subjects were 3 teachers and 90 students. The research instruments are interviews and questionnaires. The data collection technique used in this study was non-test, in the form of a questionnaire (questionnaire), and interviews. The results showed that social interaction during the pandemic was less effective. This is evidenced by five indicators. 1. Working together has an average score of 82.43%. During a pandemic, it is less effective because of limitations and many obstacles. 2. The openness of the average value of 82.43% is classified as "good", there are still many students who do not understand technology for online learning and how to use it. 3. Empathy has an average value of 80.95%, which is classified as "good". There is already awareness among students to empathize with their friends. 4. Motivating the average value of 79.70% is classified as "good", when students learn from each other, they support each other and work together in doing assignments together at home. 5. With a positive sense, with an average value of 81.56%, students are able to develop positive values that exist in the surrounding environment. 6. Similarity with others, with an average value of 82.15%, there is an attitude of equality among students to their friends working together on assignments and collecting assignments.